High prevalence of periodontitis in children and adolescents with type 2 diabetes. Issue 2 (9th November 2022) - Todescan, Sylvia M. C.; Schroth, Robert J.; Dean, Heather; Wicklow, Brandy; Michel‐Crosato, Edgard; Sellers, Elizabeth
Abstract: Background: The aim of the present study was to determine the prevalence of periodontitis in children and adolescents with type 2 diabetes, and if poor glycemic control is associated with increasing prevalence of the disease. Methods: This is a cross‐sectional study involving children and adolescents with type 2 diabetes. A questionnaire related to oral health care history and oral health behaviors was administered to each participant and they then underwent a full‐mouth oral evaluation. In addition, clinical and metabolic parameters were extracted from the clinical chart. Results: One hundred and twenty one children and adolescents (8–17 years, 11 months) participated. Overall, 45.5% presented some degree of periodontitis, with 10 (8.3%) mild, 36 (29.8%) moderate, and nine (7.4%) severe. The periodontitis group (PD‐group) had higher mean gingival and plaque indexes, periodontal probing depth, and clinical attachment loss than the group without periodontitis (NoPD‐group) ( p <0.05). A statistically significant relationship between the prevalence of periodontitis and glycosylated hemoglobin (HbA1c) was verified in the bivariate (odds ratio [OR] 1.31 [95% CI, 1.13‒1.53], p = 0.001) and multivariate (OR, 1.29 [95% CI, 1.03‒1.61], p = 0.03) analysis. For the adjustment variables, associations were verified for duration of diabetes, age, body mass index z‐score, lack of running water, insulin use, and acanthosis nigricans. Conclusions: Children and adolescents with type 2 diabetes presented high rates of periodontitis comparable with that seen in previous studies in youth with diabetes. Uncontrolled HbA1c influences prevalence of periodontal disease. The lack of matched control group and radiographs are limitations of the study. Comprehensive periodontal examination is essential for children and adolescents with type 2 diabetes to prevent, identify, and treat periodontitis early.